2006
DOI: 10.2337/dc05-2494
|View full text |Cite
|
Sign up to set email alerts
|

Health Care and Patient-Reported Outcomes

Abstract: OBJECTIVE -The purpose of this study was to assess the relationship of patients' selfreported well-being, self-management, and diabetes control with factors related to the patient's health care.RESEARCH DESIGN AND METHODS -This was a cross-sectional survey of national samples of patients with diabetes (n ϭ 5,104) from the multinational study of Diabetes Attitudes, Wishes and Needs (DAWN). Patients from 13 countries in Asia, Australia, Europe, and North America reported their level of well-being, self-managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 48 publications
4
78
0
6
Order By: Relevance
“…Therefore it is not surprising that Injection-related anxiety was one of the most common reasons for resisting the idea of starting insulin therapy. [12,13]. About one third (33.5%) of our patients reported injection phobia and 44.3% believed that insulin injections are painful.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore it is not surprising that Injection-related anxiety was one of the most common reasons for resisting the idea of starting insulin therapy. [12,13]. About one third (33.5%) of our patients reported injection phobia and 44.3% believed that insulin injections are painful.…”
mentioning
confidence: 99%
“…Norbert et al [4] have similarly demonstrated that patients on insulin treatment and those switched to insulin treatment had better appraisal of Insulin therapy than those on oral hypoglycemic agents (mean ITAS score: OAD group 53.6, switched to Insulin 46.2, on insulin at baseline group 44.5). Therefore, a negative appraisal of insulin treatment is probably modifiable by the initiation of insulin therapy and some barriers to uptake of insulin may be temporary [13]. However we were alive to considerations of the care-related context which is unique to countries and healthcare systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Os segundos prendem-se com a ansiedade induzida no do médico para tratar o doente com insulina 10 . Estas cardiovascular, particularmente nos níveis de triglicerídeos e no colesterol das HDL 6,11 .…”
Section: Introductionunclassified
“…In the global Diabetes Attitude Wishes and Needs (DAWN) study, patients who had access to diabetes team members such as nurses reportedly had better outcomes [4,5].…”
Section: Short Communicationmentioning
confidence: 99%